The Effectiveness of Jigsaw Method in Improving Students Reading Comprehension - Nurbianta Nurbianta; Hana Dahlia (Universitas PGRI Semarang, 2018)
Reading comprehension is a major objective of language instruction in English learning concept teaching in senior high school. As one of macro skill of English it is being important part in English Language Teaching. So, the teacher should teach actively to helpstudents get the ultimate goal of reading instruction. Jigsaw is one of cooperative learning which is interesting to be applied to boost students’ motivation in learning English especially to reading skill. The activities is centered to the students, so it can stimulated students activeness because they involved in active learning.Based on the tittle, the formulation of the problem was: 1) Is the prepared test curricularly valid and reliable?,2) What are the results of pretest and posttest using jigsaw method?, 3)Is there any significant difference result of pretest and posttest using jigsaw method? Design of this research was pre-experimental design by pretest-posttest one group. Research subject was students in SMPN 13 Berau while object of the research was the use of jigsaw method in reading instruction. The population of this research was 100 students of seventh grade of SMPN 13 Berau, and the sample was 30 students taken by random sampling technique. The instrument was test then analyzed by scoring, normality, homogeneity, mean, t test and hypothesis testing. The results of this research are; 1) The test instrument used in this research was appropriate in term of the objective and applicable in this particular situation because the prepared test curricularly valid and reliable, 2)The result of posttest slightly higher than pretest in conducted jigsaw method in SMPN 13 Berau, 3) There is significant difference of jigsaw method used that exists on respondents specifically students in SMPN 13 Berau during learning English as Second Language (ESL) specifically for reading instruction.The hypothesis of this researchis accepted because there is significant effect of Jigsaw Method in Improving Students Reading Comprehension to the First Grade At SMPN 13 Berau 2017/2018.